THE DEVELOPMENT OF KAMPUNG ARAB AS A TOURISM KAMPUNG IN SURABAYA - Feti Mayasari; Happy Ratna Santosa; Muhammad Faqih (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
Kampung Arab, known as a religious tourism kampung in Surabaya offers historical tourism concept, culture, and commercial activity to society in which is always crowded with tourists. Over time, the area of religious tourism is increasingly and well managed, which can be viewed in terms of area functions as a commercial area cum residential Kampung. Thus, in indirect way, tourism brings a significant impact on this region. Residents of this Kampung mostly work as merchands and open businesses in the area (residential), enabling them to expand their own business further. This change as a form of adaptation to adjust their needs. Some buildings (residential) are converted to warehouse and shops or else being reformed into a modern building, thus diminish the original character of this area. This is a quali-tative study which is focussed on the social condition of the residents. The resear-cher uses in-depth interview and observation methods. Related variables in this research is non-physical variables, include historical aspects, culture, and socio-economic, whereas physical variables include settlement patterns, land use, hierarchy of space and facade. Data analysis technique used is FGD which netting opinion technique to explore public opinion and data reduction. The results of this research is to generate criteria over tourism kampung development which combines historical, cultural (ethnical) and socio-economic (non-physical) and physical development of the Kampung Arab so that it can be sustainable tourism kampung in Surabaya which can reflect the image of the region.